Strong Earthquakes Recurrence Times of the Southern Thessaly, Greece, Fault System: Insights from a Physics-Based Simulator Application - Kourouklas, Christos; Console, Rodolfo; Papadimitriou, Eleftheria; Murru, Maura; Karakostas, Vassilios (Frontiers in Earth Science, 2021)
Recurrence time statistics of strong earthquakes above a predefined magnitude threshold on specific faults or fault segments is an important tool, that could be used in the occurrence probabilities estimation and in the improvement of Earthquake Rupture Forecasts (ERF). Observational recurrence time data are limited, due to the large times between of successive strong earthquakes in a specific fault segment. As a consequence, the development of robust statistical models is often difficult. Physics-based earthquake simulators is an powerful and innovative tool to overcome there limitations, that could provide much longer earthquake records. A physics-based simulator, which embodies well known physical processes, is applied in the Southern Thessaly Fault Zone (Greece), aiming at the investigation of the recurrence behavior of earthquakes with Mw≥6.0. The simulation is implemented after the definition of an accurate fault model, by the application of the algorithm multiple times in order to conclude in the simulated catalog that performs better in respect to the observational data. The detailed examination of the 254 earthquakes of the simulated catalog with Mw6.0 reveals that both single and multiple segmented ruptures can be realized along the study area. Results of statistical analysis of the interevent times of the Mw≥6.5 earthquakes per segment evidence quasi-periodic recurrence behavior and better performance of the Brownian Passage Time (BPT) renewal model in comparison to the Poissonian behavior.